CASE REPORT ON THE SUBJECTIVE EXPERIENCE OF YOUNG ADULT WOMEN LISTENING TO MUSIC WITH A QUANTITATIVE ELECTROENCEPHALOGRAPHY STUDY (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Introduction: many studies have proven the positive effect of listening to music on health. So far there is still limited research evaluating how the brain plays a role in supporting cognitive activity listening to music and how it affects health. One method that can evaluate brain activity in listening to music and its effects on health is by measuring electroencephalography quantitatively associated with changes in heart rate. Objective: to subjectively measure mental activity in listening to music through quantitative EEG examination by looking at the size of event related de/re-synchronization (ERD) alpha wave power and its correlation to heart rate variations in real time, in young adult women. Methods: measuring the ERD power of the alpha of the 20 EEG electrodes with variations in heart rate when the subject listens to music. Results: when listening to music there is a decrease in left prefrontal cortex activity (F3 and F7). In general, there is a lateralized pattern of increasing right hemispheric alpha power, and there is a very dominant increase in the right auricular (A2), right temporal (T6) and right occipital (O2) areas. There is no difference in heart rate frequency during basal conditions with listening to music. Conclusion: the subjective experience of listening to music is followed by lateralization of the right hemisphere with a very dominant increase in the auricular, temporal and occipital areas.
Keywords: cognitive activity; electrode; music; electroencephalography